Memulai Pola Hidup Sehat bagi Ibu Hamil dalam Upaya Kelangsungan Generasi Sehat di Desa Lubok Sukon Kecamatan Ingin Jaya Kabupaten Aceh Besar - Martina Martina; Yuli Zuhkrina; Kiki Rezeki Amelia; Lensoni Lensoni (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Stunting is a significant health issue in Indonesia caused by chronic malnutrition starting during pregnancy. A healthy lifestyle for pregnant women is an essential step to prevent stunting and support the continuity of a healthy generation. This community service activity aimed to increase the knowledge of pregnant women, prospective brides, health cadres, and the community about the importance of a healthy lifestyle during pregnancy. The activity was conducted in Lubok Sukon Village, Ingin Jaya Subdistrict, Aceh Besar District, on December 23, 2023, through counseling, interactive discussions, and free medical check-ups. A total of 84 respondents participated in this program. Based on pre-test results, only 19.04% of respondents had good knowledge about a healthy lifestyle. However, after the education, this number increased to 69.05%. The education covered topics such as nutritional intake, regular pregnancy check-ups, physical activity, and family support. The results indicate that this program effectively improved respondents' understanding. It is expected that this initiative can serve as a starting point in reducing stunting rates in the community.